Awareness, Willingness to Accept and Factors Influencing Covid-19 Vaccination Amongst Antenatal Attendees at a Nigerian Tertiary Hospital - Ozori, Ebiogbo Stanley; Akanatei, Inere Daniel; Makinde, Olakunle Ifeoluwa; Adhuze, Judith Isioma; Unachukwu, Emmanuel Chidozie; Ofuruma, Ninabai Napoleon; Osegi, Nkencho (British Journal of Healthcare and Medical Research, 2022)
COVID-19 infection can become severe in pregnancy. When fear enshrouds antenatal use of the vaccine, pregnant women and their unborn babies become at risk and at the same time act as the disease’s reservoirs. This study is aimed at determining the awareness, willingness to accept COVID- 19 vaccination among antenatal attendees as well as factors influencing COVID-19 vaccination at the Niger-Delta University Teaching Hospital, Okolobiri. The study was a descriptive cross sectional study. Three hundred and fifty pregnant women were interviewed after informed consent. The data acquired included the awareness and source of information on COVID-19 vaccine, its acceptance, reasons for vaccine hesitancy and side effects. Three hundred and thirty-eight pregnant women (96.6%) indicated awareness of the availability of the COVID-19 vaccine. Only 13 of the 350 pregnant women in this study had received the vaccine (3.7%). The television was the leading source of information about COVID-19 vaccines, (51.4%). The topmost reason for not been vaccinated was concern about the safety of the vaccines (39.2%). Age, religion, level of education and occupation were significantly associated with acceptance of COVID-19 vaccine. Eleven out of thirteen study subjects (84.6%) who have been vaccinated against COVID-19 had side effects. The commonest side effect of COVID-19 vaccination was malaise (84.6%). COVID-19 vaccine awareness in this study was optimal. However, its uptake in pregnancy was poor. Socio-demographic characteristics of antenatal attendees influences their use of COVID-19 vaccine. The COVID-19 vaccination side effects in pregnancy are mainly not life-threatening.